HUBUNGAN KUALITAS PELAYANAN KESEHATAN DENGAN TINGKAT KEPUASAN PASIEN TB PARU YANG MENJALANI PROGRAM PENGOBATAN - Henny Syapitri; Johansen Hutajulu; Novita Aryani; Frida Liharis Saragih (LPPM STIKES Muhammadiyah Kendal, 2021)
Tuberculosis is still a health problem both in Indonesian and in the world and is the leading cause of death. DOTS strategy is the tuberculosis control program. This program carried out by the health center Helvetia and the expeted number of patients with tuberculosis decreased. Quality of service is a form of activity undertaken by health services such a service, processes, and environment that meet or exceed expectations. The Satisfaction of a judgment given when the patients gets care. This study aims to determine the relationship of quality health Tuberculosis DOTS treatment strategy. The type of research used in this study is an analytic correlation using cross sectional method, samples in this study were patients who underwent Tuberculosis DOTS treatment strategy. The samples of the study was 48 respondents choose by consecutive sampling. Data were analysis of health care quality relationship with the level of satisfaction obtained significant value p = 0,003 and the value of r = 0,423. Then there is a relationship between the quality of health services with the level of satisfaction. It is advisable to further improve nursing services in order to increase the comfort and the health of patient.